IMPROVING SEVENTH GRADERS’ VOCABULARY USING FLASHCARDS AT SMP NEGERI 13 TARAKAN - Noftalia, Noftalia; Rafiqa, Syarifa; Nur Asiah, Nur Asiah (Borneo Journal of English Language Education, 2023)
English language learners possess eight essential language skills: reading, writing, and speaking. When learning English, a thorough understanding and effective use of terminology is necessary right from the start. This study examines flashcards' efficacy in English classroom education, particularly for seventh-grade students. The research included a qualitative approach and involved a literature review. According to the study's findings, utilising this specific card game as an educational tool can provide significant advantages and aid teachers in delivering instruction more effectively. Furthermore, it possesses the capacity to improve student's proficiency in the English language and to motivate pupils to participate actively in classroom activities. This will facilitate favourable interactions between professors and students and between students and the learning medium.Â